MASSIKOLA: An Innovative Learning Model to Improve Cell Concept Understanding in High School Students - Octavia, Nur Rezki; Palennari, Muhiddin (Jurnal Edukasi Terkini, 2025)
Purpose-This study aims to develop the MASSIKOLA learning model to improve the quality of biology learning in high schools. This model is designed to be able to overcome challenges such as low student motivation, lack of relevance of material to everyday life, and minimal repetition of material. In addition, this model is also expected to instill the values ​​of Sustainable Development Goals (SDGs) in the learning process. Methodology/Design/Approach-The method used in this study is a qualitative literature study. Researchers analyzed various relevant literature related to the constructivist, behaviorist, and SDGs integration approaches in biology education. The development of the MASSIKOLA model was carried out through the synthesis of these theories into nine stages of structured learning. Findings-The results of the analysis show that the MASSIKOLA model consists of nine main stages: triggering problems, problem analysis, solution studies, solution simulations or simple experiments, interpretation of simulation or experimental data, contributions to SDGs related to certain cellular/molecular/systemic biology topics; repeated observations to strengthen understanding; solution reports as a form of reflection; and real action as the implementation of knowledge to the surrounding environment. Originality/value-The development of the MASSIKOLA model not only answers the need to improve the quality of the teaching and learning process but also builds students' awareness of current global issues.